2020
DOI: 10.1158/2159-8290.cd-19-1472
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Therapeutic Interaction of WNT Pathway Activation and Asparaginase for Colorectal Cancer Therapy

Abstract: Colorectal cancer is driven by mutations that activate canonical WNT/ β -catenin sig naling, but inhibiting WNT has signifi cant on-target toxicity, and there are no approved therapies targeting dominant oncogenic drivers. We recently found that activating a β -cateninindependent branch of WNT signaling that inhibits GSK3-dependent protein degradation induces asparaginase sensitivity in drug-resistant leukemias. To test predictions from our model, we turned to colorectal cancer because these cancers can have W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 73 publications
0
41
0
Order By: Relevance
“…Similar to findings in leukemic blasts, the synergy between L-asparaginase and WNT pathway activation can also be observed in solid tumors. Similar to ALL cells, the same group found that WNT activation by R-spondin fusion in colorectal cancers drives selective sensitivity to L-asparaginase treatment [ 80 ]. Of interest, APC mutations that activate beta-catenin downstream of GSK3 shows little response to L-asparaginase treatment.…”
Section: The Role Of Asparagine In Other Types Of Cancermentioning
confidence: 99%
“…Similar to findings in leukemic blasts, the synergy between L-asparaginase and WNT pathway activation can also be observed in solid tumors. Similar to ALL cells, the same group found that WNT activation by R-spondin fusion in colorectal cancers drives selective sensitivity to L-asparaginase treatment [ 80 ]. Of interest, APC mutations that activate beta-catenin downstream of GSK3 shows little response to L-asparaginase treatment.…”
Section: The Role Of Asparagine In Other Types Of Cancermentioning
confidence: 99%
“…Similarly, by candidate-gene or comprehensive genomic analyses, other actionable targets were identified as cetuximab-resistance biomarkers, including MET Proto-Oncogene and Fibroblast Growth Factor Receptor 1 ( FGFR1 ) amplification [ 46 , 96 ], ERBB2 and MAP2K1 activating mutations [ 46 , 97 ], insulin Like Growth Factor 2 ( IGF2 ) overexpression [ 98 ], and the fusion of echinoderm microtubule-associated protein-like 4 ( EML4 ) gene with the anaplastic lymphoma kinase ( ALK ) gene leading to the production of a protein (EML4-ALK) that promotes and maintains the malignant behavior of the cancer cells [ 99 ]. More empirically, Hinze and colleagues showed that CRC PDXs displayed significant tumor responses upon Glycogen Synthase Kinase 3 α (GSK3α) inhibition combined with the anti-leukemic enzyme asparaginase [ 100 ]. However, further studies are required before the translation of such results into viable therapeutic approaches.…”
Section: Patient-derived Modelsmentioning
confidence: 99%
“…Due to this fact, these cancers become refractory to treatments with asparaginase, an enzyme that deaminates and depletes endogenous asparagine and has been long known for its therapeutic use against lymphomas (Broome, 1963a(Broome, , 1963bRizzari et al, 2013). However, recent studies have shown that forced activation of the Wnt/STOP pathway, for example by chemical inhibition of GSK3, impairs the ability of malignant cells to utilize protein degradation to obtain asparagine and sensitize them to asparaginase treatments (Hinze et al, ,2019(Hinze et al, , , 2020. Importantly, the combined treatment of asparaginase and GSK3-specific inhibitors eliminates leukemic or colorectal cancer cells in mouse models, without affecting noncancerous cells.…”
Section: Wnt a S A Me Taboli C Reg Ul Ator : Protein Turnover And Nmentioning
confidence: 99%